On the Records of Philometra sp Occurrence on Sciaenid Species - Keisham Geenita; Rajesh Kumar; Karankumar K Ramteke; Ashok Kumar Jaiswar; Muzammal Hoque (Journal of Indian Fisheries Association, 2024)
During a study on taxonomy of family Sciaenidae, two new host, Panna heterolepis and Nibea soldado for the nematode parasite Philometra sp, were recorded on specimens collected from east coast and west coast of India, respectively and also on Otolithes ruber collected from north-east coast of India. The preferred site of attachment for the parasite was found to be in the caudal fin and anal fin areas. In most cases, only one parasite was found attached on each fish, while in some few specimens, it was two parasites per fish.